Association of Serum Triglycerides and Total Cholesterol levels with Hypertension in Adult Female - Yeasmin, Nahid; Akhter, Qazi Shamima; Mahmuda, Sayeeda; Nahar, Sharmin; Abira, Mahmuda; Rahman, Farhana; Habib, Tamanna Binte; Hasan, Mahmudul; Yeasmin, Shahanara (Bangladesh Critical Care Journal, 2019)
Hyperlipidemia is one of the most widespread medical disorder in female and its complications are increasing all over the world, leading to life threatening medical problems like cardiovascular diseases, stroke and peripheral vascular diseases. An association between hyperlipidemia and hypertension has been identified. The study was carried out to observe the association of serum triglycerides and total cholesterol level with hypertension in adult female subjects. This cross sectional study was conducted in the Department of Physiology, Dhaka Medical College, Dhaka, during the period of January 2011 to December 2011. A total number of sixty female subjects were selected with age ranging from 30 to 50 years. Among them 30 female subjects with hypertension were included from the out-patient department of Medicine, Dhaka Medical College Hospital, Dhaka as study group (B) and 30 apparently healthy females were taken as control group (A) for comparison. Estimation of fasting serum triglycerides (TG) and total cholesterol (TC) levels were done by enzymatic method in the Department of Physiology, Dhaka Medical College Dhaka in both groups. Systolic blood pressure and diastolic blood pressure of all participants were recorded by standard method. Data were analyzed by Unpaired Student’s- test and Pearson's correlation co-efficient (r) test as applicable. The values of fasting serum TG level were significantly higher in subjects with hypertension than those of control. Fasting serum TC level was significantly higher in subjects with hypertension in comparison to controls also. In subjects with hypertension fasting serum TG and fasting serum TC levels were higher and showed positive correlation with systolic and diastolic blood pressure. Present study revealed that systolic and diastolic blood pressure has positive relationship with fasting serum triglyceride (TG) and fasting serum cholesterol (TC) levels. Bangladesh Crit Care J March 2019; 7(1): 35-39